Effect of Storage Temperature on Ram Seminal Plasma and Its Subsequent Use as Epididymal Tail Sperm Recovery buffer - Singh, Pawan Preet; Dar, Rameez Ali; Lone, Farooz Ahmad; Bhat, Ghulam Rasool; Yousuf, Nahida; Nisa, Masrat un (The Indian Journal of Animal Reproduction, 2024)
The study was undertaken to assess the effect of storage temperature of ram seminal plasma on its use as recovery and  activation buffer for epididymal tail sperm. Five healthy cross bred rams were selected for semen collection maintained  at Mountain Research Centre for Sheep and Goats, FVSc & AH, SKUAST-K. Semen was collected by artificial vagina  method. Seminal plasma was harvested by double centrifugation method from the semen samples. Recovered seminal  plasma was stored at two different temperatures i.e., 4°C and -20°C. Degree of ram epididymal tail sperm activation  using homologous seminal plasma stored at 4°C and -20°C was investigated. The spermatozoa recovered in both types  of seminal plasma were cold stored separately at 4°C for 72 hours. All the samples were evaluated after every 24 hours  for spermatozoa quality. The percentage of sperm motility, viability and HOST reacted populations were significantly  higher (p
Keywords: Epididymal tail sperm; Homologous Seminal Plasma; Temperature; Recovery buffer